LIPSIUS’ ‟DE CONSTANTIA”, 17TH CENTURY STILL LIFE PAINTING AND THE USE OF CONSTANCY TODAY - IACOB, Anisia (Studia Universitatis Babeș-Bolyai Philosophia, 2020)
Lipsius’ De constantia, 17th Century Still Life Painting and the Use of Constancy Today. The present article revisits the main ideas from Justus Lipsius’ De constantia in the light of the present ongoing pandemic. Through his interest for the Stoics, Lipsius was able to contribute to a more general and European interest towards this topic, reviving the Stoic philosophy under the name of Neostoicism. The influence of his ideas can be seen in some art production, especially the one that is connected to the places where Lipsius lived and it is a testimony to their popularity and the various ways of transmitting them. Even if the Stoic ideal remains an ideal, the Neostoicism of Justus Lipsius is meaningful in as much as any philosophy that deals with crises because it can help us view the text from both its relevancy and our recent general experience. The isolation, the anxiety, the uneasiness and fear are emotions that have been more or less present in our lives during this pandemic and they require a solution. Constancy is the solution that Justus Lipsius proposes.